(untitled) (Journal of Health Sciences, 2022)
Introduction: Sexual satisfaction is the pleasure an individual feels both physically and psychologically, and is the result of erotic experiences, thoughts, dreams, and autoeroticism. Purpose: The purpose of the study is to present the determinants of sexual satisfaction among Bosnian and Herzegovinian women. Methods: The survey was conducted on 387 Bosnian and Herzegovinian women via online questionnaire that consisted of demographic data and 17 statements. The validated questionnaire was used with some adaptations and contained a 5-point Likert scale for each statement, ranging from “not at all satisfied” to “extremely satisfied.” The inclusion criteria were: (a) Age 18–60 years; and (b) completion of the questionnaire as personal consent. Data were analyzed using SPSS 26.0 statistical software. Results: Data collection was conducted from July 2020 to September 2020. The realization rate of the sample was 24.19%. Most of the participants have a high school diploma, most are between 18 and 24 years old and most are currently married. Thirty-five percent of women sometimes experience pain during intercourse (less than half the time). The lower half of the vagina (from the vaginal entrance to the half of the vagina) and the lower part of the abdomen are usually most affected. A relationship was found between the number of children and sexual satisfaction. Women without children were the most satisfied with their sexual life, followed by women who had only one or two children. Conclusions: Every woman has the right to feel sexual satisfaction. The complexity of sexual satisfaction is reflected in many determinants and factors that can influence it positively and negatively.